Palbociclib: a first-in-class CDK4/CDK6 inhibitor for the treatment of hormone-receptor positive advanced breast cancer - Lu, Janice (J Hematol Oncol, 2015)
Palbociclib was approved by the FDA for use in combination with letrozole for the treatment of postmenopausal women with hormone-receptor-positive, HER2-negative advanced breast cancer as initial endocrine-based therapy. In addition, the combination of palbociclib with fulvestrant resulted in superior outcome than fulvestrant alone in those who had progressed during prior endocrine therapy. This research highlight summarized the current development of CDK4/CDK6 inhibitors and future directions in the treatment of advanced hormone-receptor-positive breast cancer.